On analytic solutions of nonlinear differential functional equations with nonlinear deviations of arguments - Pelyukh, G. P.; Samoilenko, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We obtain the conditions for existence and uniqueness of an analytic solution of a nonlinear differential functional equation with nonlinear deviations of the argument